2015
DOI: 10.1074/mcp.m114.043851
|View full text |Cite
|
Sign up to set email alerts
|

Dosage and Temporal Thresholds in microRNA Proteomics*

Abstract: MicroRNAs (miRNAs) modulate protein and mRNA expression through translational repression and/or mRNA decay. In this study, we combined SILAC-based proteomics and RNAseq to identify primary targets based on measurements of protein and mRNA repression and analysis of transcript 3UTR sequences. The primary target set was used to compare different prediction algorithms, revealing higher stringency of selection by Targetscan and PITA compared with miRanda, at the expense of higher false negatives. A key finding was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Here, by using the syngeneic 4T1 murine allograft breast cancer model, we show that the ability to grow tumor and to metastasize differs significantly among the various miR-204-5p-overexpressing clones that carries different levels of expression. Along with our observation of differential prognostic implication of miR-204-5p in TCGA dataset, our data provide evidence that the biological role of miR-204-5p may depend on the optimal saturation levels, which can explain the inconsistent reports on the role of miR-204-5p in the previous reports (36). However, further studies are required to understand the complex roles of miR-204-5p in breast cancer progression, along with its target genes selectivity or binding affinity based on the expression level.…”
Section: Discussionsupporting
confidence: 80%
“…Here, by using the syngeneic 4T1 murine allograft breast cancer model, we show that the ability to grow tumor and to metastasize differs significantly among the various miR-204-5p-overexpressing clones that carries different levels of expression. Along with our observation of differential prognostic implication of miR-204-5p in TCGA dataset, our data provide evidence that the biological role of miR-204-5p may depend on the optimal saturation levels, which can explain the inconsistent reports on the role of miR-204-5p in the previous reports (36). However, further studies are required to understand the complex roles of miR-204-5p in breast cancer progression, along with its target genes selectivity or binding affinity based on the expression level.…”
Section: Discussionsupporting
confidence: 80%
“…Although advances in bioinformatics algorithms have the potential to increase the confidence of miRNA target predictions, the reliability of most common algorithms (miRanda, PITA, and TargetScan) still display a relatively high false positive (46–63%) and false negative (44–82%) rate . Therefore, the experimental identification of physiological targets remains one of the crucial steps in miRNA research which is reflected in the multitude of studies and reviews on this subject .…”
Section: Experimental Mirna Target Identificationmentioning
confidence: 99%
“…For instance, one study suggested that transfection of miR-22 into the WM239A metastatic melanoma cell line leads to a linear increase in intracellular miR-22 levels 48 h posttransfection. [ 33 ] In this study, however, the authors used Dharmafect 1, a liposomal-based formulation for the transfection of biomolecular cargo into cell lines, as opposed to RNAiMAX and primary cells, as in our study. This difference makes direct comparisons between these two studies difficult.…”
Section: Discussionmentioning
confidence: 99%